Digital Marketing Strategy for Balinese Handicrafts Facing the Metaverse Era - Pande Devi Monica; Gede Sri Darma (Universitas Ahmad Dahlan, 2022)
The Internet has become a basic need for every individual. Especially now, the world is preparing for the metaverse era. Many segments that have experienced a shift in conventional activities have now switched to digital systems. This article aims to determine the digital marketing strategy for Balinese handicrafts in the new average era and whether the digital marketing strategy can increase sales of Balinese handicrafts in the new middle era after the pandemic Covid-19. In this study, the researcher used qualitative research with a phenomenological exploration approach using the sampling technique of snowball sampling and saturation. This study shows that perpetrators of MSMEs (Micro, Small and Medium Enterprises) in Bali have used digital marketing in marketing. The digital media used by these MSME actors are Facebook, Instagram, and WhatsApp. By utilizing the Facebook, Instagram, and WhatsApp applications as media for digital marketing strategies for handicrafts, MSME actors in Bali have increased sales of handicraft products, especially in the new normal era.